2018
DOI: 10.3390/ijms19123770
|View full text |Cite
|
Sign up to set email alerts
|

The Ambivalent Function of YAP in Apoptosis and Cancer

Abstract: Yes-associated protein, a core regulator of the Hippo-YAP signaling pathway, plays a vital role in inhibiting apoptosis. Thus, several studies and reviews suggest that yes-associated protein is a good target for treating cancer. Unfortunately, more and more evidence demonstrates that this protein is also an essential contributor of p73-mediated apoptosis. This questions the concept that yes-associated protein is always a good target for developing novel anti-cancer drugs. Thus, the aim of this review was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 133 publications
1
45
0
Order By: Relevance
“…Several studies have confirmed the oncogenic role of YAP in modulating tumorigenesis in a group of human cancers [24][25][26][27][28] . For example, YAP gene is amplified in TNBC and liver cancer.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have confirmed the oncogenic role of YAP in modulating tumorigenesis in a group of human cancers [24][25][26][27][28] . For example, YAP gene is amplified in TNBC and liver cancer.…”
Section: Discussionmentioning
confidence: 89%
“…In recent years, several studies have found that the Hippo signalling pathway can promote tumour invasion and metastasis via EMT 16‐19 . And the molecular mechanism through which the Hippo pathway activates apoptosis is realized via p73 20‐22 . According to researchers, such as Yoon et al, 23 the tumour suppressor p73 mediates apoptosis by regulating the antiapoptosis regulator Bcl‐xL.…”
Section: Introductionmentioning
confidence: 99%
“…YAP are nuclear localized in aggressive cancers. Thus, co expression of CD166 and YAP could be prognostic in cancer (Zhang et al, 2018). This study showed CD166/YAP down regulated HCC treated with HEAII and HEAIP compare to that HCC non-treatment.…”
Section: Discussionmentioning
confidence: 56%